RUMAH SENI RUANG TERAPI - Herman Suyudhi; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2020)
Stress and Depression are problems that often occur in people's lives. One of the causes is one’s habit in spending most of their time working and resting at home and without social activities that can be done every day with other individual, furthermore with the existence of social media that makes humans able to communicate with electronic devices and not meeting directly. The main issue is